The Influence of Leadership Communication in Socialization of Occupational Health and Safety Program on Employee Safety At Pt. - Muhammad Sartono Baktiar; Kukuh Sinduwiatmo (International Journal on Orange Technologies, 2021)
Worker activities are very important for the company's productivity, especially for largescale industrial sectors such as PT. Pabrik Kertas Indonesia, Mojokerto. For the smoothness production process, the workers are accompanied by factor of Occupational Health and Safety. The OHS program is also run by every division in the company as in the Heavy Equipment Pool (HEP) section. The purpose of this research is to find out the influence of heavy equipment pool leaders on employee safety simultaneously and partially with the theory of superior communication in organizational communication. This quantitative research uses statistical testing of two variables namely independent variable (X) and dependent variable (Y). the independent variable used by researchers is leadership communication (X), while the dependent variable is employee safety (Y). This research is in the Heavy Equipment Pool (HEP) section of PT. Pakerin in the Bangun, Pungging Mojokerto. This study used 50 respondents to answer the questionnaire given. The results of the questionnaire were then processed using simple linear regression analysis techniques using the SPSS 16.0 program. The results showed that there is an influence of leadership communication in the socialization of OHS program on employee safety at HEP of PT. Pakerin is positive and significant with R of 0.285 which belongs to the weak category. The amount of influence or determination value (R square) is indicated at 8.1%. From the results of the F test and T Test can be concluded that H1 can be accepted with the meaning of communication leadership has an influence in the socialization of the OHS program on the safety of employees in the Heavy Equipment Pool section of PT. Pakerin Mojokerto